A study on the sustainability of large sporting events and host cities-the Harbin Asian winter games as an example - Wu, Fengyu; Zheng, Guohua (Edelweiss Applied Science and Technology, 2024)
This paper delves into the relationship among major sports events and urban sustainability. The paper takes case study of the Asian winter games in Harbin, China. This paper also explores the effects of support events and presents pragmatic policy options for those countries opting to host significant sporting events. Major sports events have a wider audiences, which offers huge potential for advancing sustainable development in urban societies. The key objectives of the paper is to find out the effects of major sporting events on urban sustainable development using the Asian winter games in Harbin as an example. Important insights explain the important of support events. It aims to enhance the city’s outlook. Moreover, it promote economic progress, and raise the standard of living for its people. This paper highlights the significant opportunity large-scale sports events present for urban sustainable development while underscoring the importance of planning, management, and evaluation. ‘The winter games of Asia presents important lessons for other cities to achieve sustainable development goals better, ensuring the success of hosting major sports events aligns with the city’s sustainable development. The results of this paper provide helpful guidance for later similar paper and pragmatic utility.